Investigating the Integration of Nanotechnology and Fabric Art in the Metaverse - Jeyranzadeh, Raziyeh; Zohoori, Salar; Davodiroknabadi, Abolfazl; Jahangard, Aliakbar (Management Strategies and Engineering Sciences, 2025)
The purpose of this study is to identify and rank the most effective pricing strategies for innovative products in the Iranian market, with an emphasis on key influencing factors and the provision of a scientific framework for managerial decision-making. To this end, the main research question focused on determining the most critical factors affecting the selection of the optimal pricing strategy and how these factors can be applied within a systematic framework. The methodology employed was the Fuzzy Analytic Hierarchy Process (FAHP), which enabled precise prioritization of options based on multiple criteria and expert judgment. The statistical population of the study consisted of 10 individuals, including senior marketing managers and experts from companies active in the field of innovative products, as well as academic specialists in business management and marketing. The main criteria and sub-criteria were considered across four key dimensions—innovation (product development capability, life cycle, degree of innovativeness), marketing (target markets, launch timing, market scope, growth), product (ease of use, after-sales support, branding, patent protection), and technology (payment channels, consumption convenience, technological uniqueness). Six pricing strategies were evaluated as decision-making options: prestige pricing, versioning, windowing, exclusive products, fixed pricing, and dynamic pricing. Findings from the FAHP analysis revealed that prestige pricing (weight = 0.444) is the most suitable strategy for innovative products in the Iranian market. Versioning ranked second with a weight of 0.268, while other strategies such as windowing, exclusive product pricing, fixed pricing, and dynamic pricing occupied the subsequent ranks, respectively. The results, in addition to providing a clear picture of the prioritization of pricing strategies, confirm the use of fuzzy multi-criteria decision-making models as an effective tool for analyzing marketing challenges in the context of the Iranian market. These findings offer practical and scientific guidance for managers, policymakers, and researchers in the domain of innovative product pricing.